Seven up acts as a temporal factor during two different stages of neuroblast 5-6 development. - Benito-Sipos, J.; Ulvklo, C.; Gabilondo, H.; Baumgardt, M.; Angel, A.; Torroja, L.; Thor, S. (Development, 2011)
Drosophila embryonic neuroblasts generate different cell types at different time points. This is controlled by a temporal cascade of Hb?Kr?Pdm?Cas?Grh, which acts to dictate distinct competence windows sequentially. In addition, Seven up (Svp), a member of the nuclear hormone receptor family, acts early in the temporal cascade, to ensure the transition from Hb to Kr, and has been referred to as a 'switching factor'. However, Svp is also expressed in a second wave within the developing CNS, but here, the possible role of Svp has not been previously addressed. In a genetic screen for mutants affecting the last-born cell in the embryonic NB5-6T lineage, the Ap4/FMRFamide neuron, we have isolated a novel allele of svp. Expression analysis shows that Svp is expressed in two distinct pulses in NB5-6T, and mutant analysis reveals that svp plays two distinct roles. In the first pulse, svp acts to ensure proper downregulation of Hb. In the second pulse, which occurs in a Cas/Grh double-positive window, svp acts to ensure proper sub-division of this window. These studies show that a temporal factor may play dual roles, acting at two different stages during the development of one neural lineage.